Rastreio de doença coronária no diabético assintomático. Como e em quem? - Matos, P (2014)
Screening for coronary artery disease (CAD) in the asymptomatic diabetic patient is controversial with respect to both patient selection and rational choice of screening methods. Epidemiological studies in the real world and improved knowledge on risk markers have changed the criteria that help refine global risk stratification in a patient population that is per se high risk. Over the past years, it is likely that we have been overestimating the risk when using the classical risk factors. This review highlights the role of novel risk markers in the global assessment of diabetic patients, and identifies the best diagnostic approaches to select those patients who might benefit most from revascularization procedures or more aggressive treatment goals, despite the absence of symptoms. Factors such as the presence of kidney disease, cardiovascular autonomic neuropathy or atherosclerotic disease in other arterial territories, may exponentially increase the risk of poor outcomes in diabetic patients. With the aim of rationalizing the use of diagnostic procedures, we propose a sequential approach that combines anatomic and functional data with the coronary calcium score. This approach may serve as a filter to select patients for further assessment with more expensive and less available tests so as to optimize the cost-benefit ratio of screening.